A Study of Self-Regulation on Online Game Addiction in Kupang City - Aditya Rinaldi. S Lay; M. K. P. Abdi Keraf; R. Pasifikus Christa Wijaya (Universitas Nusa Cendana, 2021)
According to data released by the Ministry of Communication and Information through its official website in 2015, it is estimated that more than 100 million of the approximately 250 million Indonesian citizens became active smartphone users in 2018 (KOMINFO, 2015). The survey results stated that as many as 54.68%, namely 143.26 million people from the total population of Indonesia's 262 million people, were internet users. Online games continue to grow among teenagers because they can be played online via the internet. Online games are a type of computer game that utilizes a computer network (LAN or internet) as a medium (Young, 2006). This study describes the effect of self-regulation (short-term and long-term) on online game addiction in adolescents who join the E-Sport Community in Kupang City. The sampling technique used total sampling with a total sample of 488 participants and then analyzed using Structural Equation Modeling (SEM). This research shows that there is a significant influence between self-regulation (short-term and long-term) on online game addiction